Evidence of occult right ventricular dysfunction in morbidly obese patients. (25th November 2020) - Samuel Kulifay, S.L.K; Dominic Lattanzio, D.S.L; Brandon Mikolich, B.M.M; Ronald Mikolich, J.R.M
Abstract: Background: Abnormalities of right ventricular (RV) strain have been shown to occur prior to impairment of global right ventricular function, measured by global RV ejection fraction (RVEF) in patients with increased RV afterload, such as pulmonary hypertension. Obesity is a form of increased afterload involving both the right and left cardiac circulations, raising suspicion that impaired RV strain may be an early indicator of myocardial dysfunction. Purpose: This study was designed to assess impairment of RV strain in obese patients with normal right ventricular ejection fraction (RVEF) using cardiac MRI Fast SENC (strain encoded) pulse sequences. Methods: An institutional cardiac imaging database was queried for all patients with body mass index (BMI) greater than 35 kg/m 2 who underwent measurement of RV global longitudinal strain (GLS), RV global circumferential strain (GCS) and 37 segmental strain measurements using cardiac MRI Fast-SENC pulse sequences. Global RVEF was computed for all patients using a standard cardiac MRI method using non-automated hand drawn RV endocardial borders. Global and regional strain measurements were compared to a cohort of healthy volunteers who also underwent CMR Fast-SENC imaging. Abnormal myocardial strain was defined as a value greater than −17%. Results: Of the 356 patients in the database, 48 had a BMI greater than 35 kg/m 2 . Mean RV GLS and GCS for the study cohort were −16.6 and −15.8 respectively. For healthy volunteers RV GLS and GCS were −20.8 and −19.0 respectively. Comparison of mean RV GLS and GCS of both groups were statistically significant ANOVA p<0.001. The number of normal RV segmental strain values was significantly decreased in obese patients when compared to the normal cohort, ANOVA p<0.001 (Figure 1). Furthermore, the prevalence of abnormal RV GCS in morbidly obese patients with normal RVEF greater than or equal to 40% was 84% (21 of 25 patients). Conclusions: These findings suggest that morbidly many obese patients have occult RV dysfunction despite a normal RVEF. This occult RV dysfunction not only affects RV global GLS and GCS, but also the percentage of normal segmental strain values. Detection of occult RV dysfunction is of clinical significance in that it may provide an opportunity for treatment before development of symptomatic right heart failure. Funding Acknowledgement: Type of funding source: None